Motivasi Lansia Pria dalam Melakukan Olahraga Bulutangkis di Kecamatan Prambon, Kabupaten Nganjuk, Jawa Timur Tahun 2024: Motivation of Elderly Men in Playing Badminton in Prambon District, Nganjuk Regency, East Java, in 2024 - Thoriq Al Farah, Ahmad; Yuliawan, Dhedhy; Burstiando, Riski (CV. Nusantara Sporta, 2025)
This study aims to analyze the motivation of elderly men in playing badminton in Prambon District, Nganjuk Regency, East Java. Motivation is a crucial factor in sustaining physical activity among the elderly, especially in high-intensity sports like badminton. This research employs a quantitative approach using a survey method with questionnaires. The study sample consists of 32 elderly men who actively play badminton. Data were analyzed using descriptive statistics to examine the trends in intrinsic and extrinsic motivation. The results indicate that intrinsic factors have the highest relative frequency in the